Mathematics Learning with Scramble Model and Snakes and Ladders Media: Pembelajaran Matematika dengan Model Scramble dan Media Ular Tangga - Rahmadhani, Sri; Wahyu Hidayat, Puput; Sundahry (Academia Open, 2025)
General Background: Mathematics learning in elementary schools often fails to engage students, leading to low motivation and unsatisfactory outcomes. Specific Background: At SDN 71/II Sungai Gambir, fourth-grade students showed limited participation and low test scores in mathematics, particularly in fractions. Knowledge Gap: Traditional methods often overlook playful and interactive approaches that align with students’ cognitive and social needs. Aims: This study examined the application of the Scramble learning model supported by Snakes and Ladders media to strengthen mathematics learning among fourth-grade students. Results: Conducted through Classroom Action Research across two cycles, findings revealed progress in teacher performance (77.27% to 90.90%), student participation (65% to 85%), and test achievement (55% to 80%). Novelty: The integration of game-based media with a cooperative Scramble model demonstrated a unique strategy for fostering active, enjoyable, and meaningful mathematics learning in elementary settings. Implications: These findings suggest that teachers may adopt interactive and playful methods to improve classroom dynamics, strengthen student collaboration, and achieve better mathematics learning results. <article class="text-token-text-primary w-full focus:outline-none scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-68b59e44-b264-832f-95fe-acf794d77a3e-1" data-testid="conversation-turn-10" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:32rem] @[34rem]:[--thread-content-max-width:40rem] @[64rem]:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-5" dir="auto" data-message-author-role="assistant" data-message-id="ce596609-58a2-4c8d-8725-75f1b726105a" data-message-model-slug="gpt-5"> Highlight: Improved teacher performance, student participation, and test scores. Scramble model combined with Snakes and Ladders created active and fun learning. Results show mathematics learning became more meaningful and engaging. Keywords: Scramble Learning Model, Snakes and Ladders, Mathematics Learning, Student Participation, Elementary Education